The role of internal audit in the effectiveness and efficiency of evaluating institutional performance: Applied study at Al-Nahrain University (Entrepreneurship Journal for Finance and Business, 2025)
The internal audit function is considered one of the basic functions in institutions because it is a source of information and data that is characterized by its credibility, and because it is a review and monitoring process of all the financial and non-financial operations of the institution in terms of discovering errors and shortcomings or even fraud and manipulation operations, and that one of the most important goals of the institution is its survival and continuity, and for this reason it led to the emergence of the internal audit function, and that the success of any institution lies in the success of its administrative and financial performance evaluation systems as it is the mirror reflecting the evaluation of actual performance compared to the planned performance of the institution.The research aimed to determine the extent of the necessity of the internal audit function and performance within institutions, and the extent of the ability of institutions to achieve the desired goals through the optimal use of available resources. A set of tools were used, the most important of which were Arabic and foreign books, theses and dissertations in their theoretical aspect, while the practical aspect was the method of direct interviews with the working staff in the department who are specialists, observations and inquiries. Among the most important conclusions reached is that work is not done according to the schedule of tasks, as all the working staff in the department carry out all the work, and the organizational structure prepared by the Studies and Planning Department is not adhered to, as it was found that the Graduates and Certifications Division was merged in terms of work with the Registration and Acceptance Division.Among the most important recommendations is obligating the department’s staff to implement the work according to the tasks assigned to each division and to work according to the tools of internal control (separation of responsibilities), obligating the divisions to the organizational structure in order to determine responsibilities and provide procedures that do not allow any staff to violate internal control. In short, the internal audit function contributes to achieving the effectiveness and efficiency of institutional performance by evaluating its operations and submitting the results of its work in the form of periodic reports to the institution’s senior management. Keywords: Auditing, internal auditing, effectiveness, efficiency, institutional performance.